An updated checklist of bryophytes for the state of Paraíba, a Brazilian hotspot: new records and biological spectrum in a Seasonally Dry Tropical Forest fragment - Fernandes De Souza, Evyllen Rita; Silva, Joan Bruno; Pinto, Anderson Silva; Lopes, Sérgio De Faria (Phytotaxa, 2021)
As a result of bryological explorations in the the state of Paraíba (Brasil), a total of 36 bryophtes belonging to 18 genera and 14 families were identified from a Seasonally Dry Tropical Forest fragment. Of these, 17 taxa are liverworts and 19 taxa are mosses. In addition, we added nine new records for the bryophyte flora of state of Paraíba with this paper. Among them, two mosses (Rhodobryum roseum and Cryphaea filiformis) and two liverworts (Caudalejeunea lehmanniana and Cheilolejeunea conchifolia) are for the first time in dry tropical forest.